Osteolipoma of the buccal mucosa - Castro, Alvimar Lima de [UNESP]; Castro, Eni Vaz Franco Lima de; Felipini, Renata Callestini [UNESP]; Ribeiro, Ana Carolina Prado; Soubhia, Ana Maria Pires [UNESP] (Medicina Oral S L, 2010)
Lipomas are benign mesenchymal neoplasms of soft tissue that can be found in any part of the human body. Conversely, their presence in the oral mucosa is rather uncommon, with approximately 4% of the cases occurring in the oral cavity. In such cases, they are likely to have originated from mature adipose tissue and to be among several described histological variants of lipomas, which are identified according to the predominant type of tissue. There is a rare lipoma, known as an osteolipoma or an ossifying lipoma; however, little has been written this type of lipoma characterized by a classical lipoma with areas of osseous metaplasia. Considering the few cases of oral osteolipomas previously described in the English-related literature and the consequent risk of misdiagnosis and overtreatment, this paper describes an extreme case of an osteolipoma affecting the buccal mucosa of an adult patient. This paper focuses particularly on the pathogenesis of this lesion and the discussion of a correct diagnosis.
Keywords: Lipoma; lipomatous tumors; osteolipoma; metaplasia